Open Versus Fenestrated Endovascular Repair of Complex Abdominal Aortic Aneurysms. Issue 5 (May 2020) - O'Donnell, Thomas F. X.; Boitano, Laura T.; Deery, Sarah E.; Schermerhorn, Marc L.; Schanzer, Andres; Beck, Adam W.; Green, Richard M.; Takayama, Hiroo; Patel, Virendra I.
Abstract : Objective: To compare outcomes of fenestrated (FEVAR) and open repairs of complex abdominal aortic aneurysms (cAAA). Background: FEVAR has emerged as an alternative to open surgery for treating cAAA, but direct comparisons are limited. Methods: We studied all repairs of intact or symptomatic cAAA in the Vascular Quality Initiative between 2012 and 2018, excluding chimney/snorkels and any devices implanted under Investigational Device Exemption studies. We compared open repairs, commercially available FEVAR devices and physician-modified endografts (PMEG) using inverse probability weighting. As a secondary analysis, we compared PMEG separately. Results: We identified 3253 cAAA repairs: 2125 open (65%), 877 FEVAR (27%), and 251 PMEG (8%). Patients undergoing FEVAR were older, with larger aneurysms, and more comorbidities. Propensity-weighted perioperative mortality was similar between open repair and FEVAR (4.7% vs 3.3%, respectively, P = 0.17), but open repair was associated with higher rates of myocardial infarction (5.0% vs 3.0%, P = 0.03), acute kidney injury (25% vs 16%, P < 0.001), and new dialysis (4.3% vs 2.1%, P = 0.003). However, propensity-weighted long-term mortality was higher following FEVAR [Hazard Ratio (HR) 1.7 (1.1–2.6), P = 0.02]. Although outcomes of commercially available FEVAR and PMEG were similar, there was a trend toward higher long-term mortality with PMEG compared to FEVAR [HR 1.7 (0.9–3.1), P = 0.09). Conclusions: In patients undergoing cAAA repair, open surgery was associated with higher overall survival than FEVAR and similar perioperative mortality, but longer lengths of stay, and higher rates of postoperative renal dysfunction and MI. PMEG were associated with similar perioperative results as commercially available FEVAR, but further study is needed to establish their long-term durability.